(untitled) (Boca Raton, FL, 2010)
This volume, Video, Speech, and Audio Signal Processing and Associated Standards, provides thorough coverage of the basic foundations of speech, audio, image, and video processing and associated applications to broadcast, storage, search and retrieval, and communications.
Keywords: Signal processing,Speech processing systems,Digital video,Xử lý tín hiệu,Viđêô số; Digital techniques,Standards,Standards,Standards,Kỹ thuật số,Tiêu chuẩn,Tiêu chuẩn